Cooperative Spectrum Sensing Based on HML and Vector Quantization for Cognitive Radio Networks - Alpna, Shweta; Mukherjee, Amrit; Datta, Amlan (International Journal of Engineering and Technology, 2018)
The proposed work illustrates a novel technique for cooperative spectrum sensing in a cognitive radio (CR) network. The work includes an approach of identifying secondary users (SUs) based on Hierarchical Maximum Likelihood (HML) technique followed by Vector Quantization. Initially, the arrangement of the SUs are been observed using HML with respect to a spatial domain and then the active SUs among them are identified using VQ. The approach will not only save the energy, but the decision of the real-time and dynamic cooperative communication network becomes more accurate as we can predict the behavior of SUs movement and spectrum sensing by each individual SU at that particular Â place. The results and simulations of the real-time experiment justifies with the proposed approach.Â